The Diversity of Terrestrial Ferns in the Customary Forest of Depati Karo Jayo Tuo, Jambi - Nazila, Jumiatun; Husnudin, Uni Baroroh; Ihsan, Mahya; Hariyadi, Bambang; Maritsa, Hasna Ul (Al-Hayat: Journal of Biology and Applied Biology, 2024)
The Depati Karo Jayo Tuo Customary Forest represents a rich ecosystem of Sumatran rainforest biodiversity. Observations reveal dense canopy cover and various terrestrial fern species, yet information regarding the diversity of terrestrial ferns remains limited. Exploratory research is essential to uncover the biodiversity of terrestrial ferns in this area, including their conservation to support effective conservation strategies, protect species and ecosystems. This study aims to identify the diversity of terrestrial fern species and evaluate their conservation status. The research employs the cruise method in the trekking path of the forest. Environmental factors measured include soil temperature, soil moisture, pH, air temperature, humidity, and light intensity. Species identification is based on the identification keys of ferns. Conservation status was analyzed based on IUCN and CITES. The study found 49 species divided into Filicinae class (45 species, 24 genera, 18 families, 5 orders) and Lycopodiinae (4 species, 1 genus, 1 family, 1 order). According to the IUCN, 32 species are categorized as Not Evaluated, 2 species as Least Concern (LC), and 15 species remain uncategorized. CITES data revealed that one species is listed under Appendix II, so it is important to protect biodiversity in the Depati Karo Jayo Tuo Customary Forest.